A novel splice donor mutation in DCLRE1C caused atypical severe combined immunodeficiency in a patient with colon lymphoma: case report and literature review - Zhang, Xiaoqing; Jiang, Wujun; Jin, Zhongqin; Wang, Xueqian; Song, Xiaoxiang; Huang, Shan; Zhang, Min; Lu, Huigang (Frontiers in Oncology, 2023)
Introduction Hypomorphic mutations of DCLRE1C cause an atypical severe combined immunodeficiency (SCID), and Epstein-Barr virus (EBV)-related colon lymphoma is a rare complication. Case presentation A teenage boy presented with colon EBV-related colon lymphoma, plantar warts, and a history of recurrent pneumonia. His peripheral blood lymphocyte count and serum level of immunoglobulin (Ig) G were normal, but he exhibited a T+B-NK+ immunophenotype. Genetic analysis by whole exome sequencing revealed compound heterozygous mutations of DCLRE1C (NM_001033855.3), including a novel paternal splicing donor mutation (c.109 + 2T>C) in intron 1, and a maternal c.1147C>T (p.R383X) nonsense mutation in exon 13. Based on his clinical features and genetic results, the diagnosis of atypical SCID with colon lymphoma was established. Our review shows that seven patients, including our patient, have been reported to develop lymphoma, all with hypomorphic DCLRE1C mutations. Among these cases, six had EBV-related B-cell lineage lymphoma, and one had Hodgkin lymphoma with EBV reactivation. Unfortunately, all of the patients died. Conclusion Recognizing the radiosensitivity of the disease is critical for the prognosis. Hematopoietic stem cell transplantation before being infected with EBV is an optimal treatment.